PERILAKU KOMUNITAS MUSLIM DALAM MENGONSUMSI PRODUK HALAL DI PROVINSI BALI - Fauziah Fauziah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
This research explores the moslem community in Bali who consume halal products by using qualitative approach. In general, understanding of the moslem community in Bali toward halal products is quite high. They always check halal label before they decide to buy the products. There is strong relations between understanding and consuming halal products. If they have high understanding, so they behave carefully in consuming halal product. Beside that, there are supporting and obstructing factors for those community to consume halal product.